Digital Translation Literacy of Undergraduate EFL Students - Fahmi, Fahmi; Arjulayana, Arjulayana (Universitas Tidar, 2023)
Abstract Literacy is the representation of language competency, individual skill in reading, writing, speaking, and managing. In digital era, literacy can be represented through the use of Google translation tool as one of the most popular tools among EFL students, either for their translation assignment or improve foreign language skills. This study aimed to explore undergraduate EFL student’s digital literacy by using Google translate as a tool to do translation. Qualitative descriptive method is used to present the data comprehensively. The data collection begin from problem identification, field observation, interview, and study the document related to their assignment. This research used purposive sampling which involved 31 EFL undergraduate students of Muhammadiyah Tangerang University. This research shows that EFL undergraduate students are able to operate and use Google translate effectively in assisting assignment. Google translate tool can eliminate the learning’s gap among different level of student’s English competency especially in vocabulary mastery and time management, the research also shows student’s digital literacy through Google translate not only for written translation, but also orally and can be used in diversity functions, such as translating the language in sentence form and learning how to pronounce English words. Keywords: Literacy, translation, Google translate, EFL students, digital literacy